Longitudinal prospective anthropometric evaluation in Caucasian prepubertal children with lactose intolerance - Lizzi, Mauro; Sgrazzutti, Laura; Porreca, Annamaria; Di Filippo, Paola; Cauzzo, Chiara; Di Pillo, Sabrina; Chiarelli, Francesco; Attanasi, Marina (Frontiers in Pediatrics, 2023)
The consequences of lactose intolerance on health are unclear. We studied the associations of lactose intolerance with growth in children. Methods: Caucasian prepubertal children with lactose intolerance (n=30, median age 7.87 years [3.00-12.75]) were compared to healthy controls (n=75, 2.25 years [2.00-7.25]) in a prospective case-control study. A lactose tolerance test was performed to diagnose lactose intolerance. Gastrointestinal symptoms score was administered at baseline and after a median period of 9.0 months (range 5-95% (6.0-24.0)) of lactose-free diet. Anthropometric parameters were measured at baseline and at the follow-up visit. All anthropometric data were converted in standard deviation scores (SDS). A linear regression model was used to investigate the associations of lactose intolerance with growth parameters. Results: Lactose intolerant children showed no difference for height velocity SDS than controls (SDS difference (95% CI) 0.52 (-1.86; 2.90)). Additionally, we found a significant reduction of clinical score in LI children after lactose-free diet (median (5-95% range) 7.5 (4.0-15.0) and 3 (0.0-8.0); p value<0.001). Conclusions: LI children showed no difference in height velocity compared with controls. Still, due to the small sample the results concerning the anthropometric profile of children with LI require careful interpretation. We need further larger studies in pediatric population to better investigate the association of LI with anthropometric and metabolic profiles.